VD_FINDINFO Décision / 2014 / 351 vom 2. Dezember 2013 - VD Tribunal cantonal (2013)
CONTRAINTE SEXUELLE, VIOL, SURSIS PARTIEL À L'EXÉCUTION DE LA PEINE | 189 al. 1 CP, 190 al. 1 CP, 43 CP, 49 al. 1 CP